PENGARUH MODAL SOSIAL TERHADAP PERTUMBUHAN EKONOMI PROVINSI DI INDONESIA: ANALISIS DATA SUSENAS 2009 - Suryanggono, Bambang (KINERJA, 2013)
The objective of this study is to ne out the effect of social capital on economic growth in all the provinces ofIndonesia. By using cross-sectional data from all the provinces of Indonesia, it can be concluded as follows:(1) The values of the stock of social capital in the provinces of Indonesia were on average 68.80 indicating thatsocieties in Indonesia have relatively good social capital. (2) Trust has the dominant contribution comparedwith other subdimension of social capital. (3) Regions with Javanese cultural values have the high stock ofsubdimension of trust on apparatus and group; the low stock of subdimension of trust on neighbor occurred inareas with social con icts caused societies tending to be careful and alert on their surrounding environment;the low stock of subdimension of religious and ethnic tolerance occurred in regions applying Islamic shariain local regulations due to lack of accuracy in implementation; the high stock of subdimension of solidarityoccurred in areas with the high level of familial relationship; egoism and individualist attitude will cause thelow stock of subdimension of networks. (4) Typological analysis indicates that 66.67 percent of provinces inIndonesia described the pattern of relationship between social capital and economic growth. (5) The stock ofsubdimension of solidarity and the stock of subdimension of religious and ethnic tolerance has a signi cantpositive effect on GRDP per capita; the stock of subdimension of trust on apparatus and group as well as thestock of subdimension of networks have a quadratic function pattern and have a signi cant effect on GRDP percapita; meanwhile, the stock of subdimension of trust on neighbor has a quadratic function pattern and has nosigni cant effect on GRDP per capita.Keywords: Social Capital, Economic Growth, Indonesia.